ANALYSIS OF MOTIVATION AND PERCEPTION OF BECOMING A BANK CUSTOMER BETWEEN PARENTS (MOTHERS AND FATHERS) AND THEIR TEENAGE CHILDREN - Aripin, Zaenal; Kosasih; Paramarta, Vip (Journal of Economics, Accounting, Business, Management, Engineering and Society, 2023)
Beckground: Perceptions and motivations to become a bank customer can be influenced by various factors, including age, experience and financial needs. Parents and teenagers have differences in life experiences, knowledge and financial priorities, which may affect how they perceive the importance of being a bank customer. This study will identify differences and similarities in motivations and perceptions between parents and adolescents in relation to becoming a bank customer. Aims: The aim of this study is to gain a better understanding of the factors that influence the motivations and perceptions of becoming a bank customer between parents (mothers and fathers) and their adolescent children. It also aims to explore the differences and similarities in their views towards becoming bank customers. Research Methods: This study used a qualitative approach with in-depth interviews as the data collection method. The research participants consisted of parents (mothers and fathers) and their teenage sons and daughters who are bank customers. Data obtained from the interviews were analyzed using an inductive approach to identify emerging themes and patterns related to their motivations and perceptions of becoming bank customers. Results and Conclusions: Data analysis revealed differences in the motivations and perceptions of becoming a bank customer between parents and their adolescent children. Parents tend to have more motivations related to financial security, long-term investment, and fulfilling family needs. Meanwhile, teenagers tend to have more motivations related to personal needs, money management skills, and financial independence. Colntributioln: This study colncludels that thel moltivatiolns and pelrcelptiolns olf belcolming a bank custolmelr diffelr beltweleln parelnts (molthelrs and fathelrs) and thelir telelnagel childreln. This diffelrelncel may bel duel tol diffelrelnt lifel elxpelrielncels, knolwleldgel, and financial priolritiels beltweleln thelsel twol grolups. This relselarch prolvidels uselful insights folr financial institutiolns in delsigning molrel elffelctivel markelting stratelgiels tol attract bolth grolups as bank custolmelrs.